2022
DOI: 10.3389/frvir.2022.890700
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality and Productivity in Knowledge Workers

Abstract: Productivity has a significant impact on success and monetary wellbeing of every organisation. Over the past few years, the substantial developments of digital technologies have encouraged a shift in the way we work and produce, from an office-based environment to “virtual work”. However, very little is known as to how virtual work and productivity can be supported by virtual reality (VR). We conducted two studies to extend previous productivity research in relation to VR: Study one examined the routes that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…can have a significant impact on teamwork and task work success. These findings are in alignment with previous work; for example, in our previous work [27], we showed that VR can enable joyful, energized teamwork sessions, with personalized avatars being a significant contributor to team cohesiveness, while the challenges that need resolution to permit effective collaboration in VR include lighter hardware and improved comfort, as well as adequate technology and tool implementations, alongside VR spaces that enable both teamwork and task work.…”
Section: Pillars Of Success: Collaborationsupporting
confidence: 91%
See 2 more Smart Citations
“…can have a significant impact on teamwork and task work success. These findings are in alignment with previous work; for example, in our previous work [27], we showed that VR can enable joyful, energized teamwork sessions, with personalized avatars being a significant contributor to team cohesiveness, while the challenges that need resolution to permit effective collaboration in VR include lighter hardware and improved comfort, as well as adequate technology and tool implementations, alongside VR spaces that enable both teamwork and task work.…”
Section: Pillars Of Success: Collaborationsupporting
confidence: 91%
“…Firstly, VR needs to account for several activities and work arrangements, including individual working, distributed collaboration, and in-office work. We know from previous research [27,28] that productivity is a multifaceted concept, largely depending on deadlines, knowledge workers' mental states (e.g., attention, motivation); the type of task (single tasks versus multi-tasking); and self-regulation behavior (e.g., task tracking versus external validation). It is, furthermore, shaped and impacted by synchronous and asynchronous collaboration, and the visibility of other team members' availability and working progress, through information sharing and project management and execution.…”
Section: Nature Of Workmentioning
confidence: 99%
See 1 more Smart Citation